PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR MENJAHIT KEMEJA DI KELAS TATA BUSANA FASE F SMK NEGERI 8 SURABAYA - Widyana Putri, Endah; Mayasari, Peppy; Nashikhah, Ma’rifatun; Marniati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
The objectives of this study are to: 1) ascertain the relationship between the PjBL learning model and the learning outcomes of sewing shirts; 2) ascertain the learning outcomes of sewing shirts following the application of the PjBL learning model; and 3) ascertain the ways in which the PjBL learning model affects the learning outcomes of sewing shirts. This research used a quasi-experimental design type by implementing a pre-experimental design. Involving research subjects as many as 29 fashion students phase f SMKN 8 Surabaya. approaches for gathering data, such as learning outcome assessments and observation. Research tools that include test and observation sheets. A straightforward linear regression test is used as a technique for data analysis. The investigation's findings demonstrated that 1) the PjBL learning model was used in sewing shirts and achieved an average of 95% with a very excellent category, and 2) learning outcomes in sewing shirts increased following the When the PjBL learning model was used, the cognitive domain received an average score of 86 compared to 77.65, and the psychomotor domain obtained an average score of 88.31 as opposed to 76.10. 3) The learning was influenced by the PjBL learning paradigm outcomes in sewing shirts, using 0.029 <0.05 as the significance value.